2021
DOI: 10.1177/01902725211030252
|View full text |Cite
|
Sign up to set email alerts
|

Social Bonding in Initial Acquaintance: Effects of Modality and Modality Order

Abstract: In this experimental study, unacquainted dyads engaged in a get-acquainted task using two modes of communication across two segments of interaction. The dyads either first disclosed in text-based computer-mediated communication (CMC) and then disclosed face-to-face (FtF) or the reverse. The participants completed reaction measures after each segment of interaction. After the first segment, dyads who communicated FtF reported more positive outcomes (e.g., liking, closeness) than dyads who engaged in CMC. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Although this premise is empirically supported (e.g., ref. 39 ), first impressions are also bound to change, as reflected by the overall small-to-moderate effect sizes in the current study. For example, research suggests that relationship effects wax and partner effects wane as people get to know each other ( 14 , 40 ).…”
Section: Discussionmentioning
confidence: 50%
“…Although this premise is empirically supported (e.g., ref. 39 ), first impressions are also bound to change, as reflected by the overall small-to-moderate effect sizes in the current study. For example, research suggests that relationship effects wax and partner effects wane as people get to know each other ( 14 , 40 ).…”
Section: Discussionmentioning
confidence: 50%
“…A common comparison is between dyads becoming acquainted face-to-face (FtF) versus in text-based computer-mediated communication (CMC). Generally, if the period of getting acquainted is brief (such as in a lab session), dyads interacting in CMC-text experience less liking and closeness than dyads interacting FtF (Okdie et al, 2011;Sprecher, 2014Sprecher, , 2021b. A few studies, however, have found greater liking and other positive impressions formed in the get-acquainted process that occurs over CMC than in FtF.…”
Section: Becoming Acquainted Onlinementioning
confidence: 99%